1980
DOI: 10.1002/ange.19800920113
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvaleno‐paracyclophane

Abstract: Beweisend fur die Ringverkniipfung in (4) und (5)141 sind vor allem die NMR-Kopplungen zwischen H' und H2 (Tabelle I), die den Diederwinkeln von ca. 180" in (4) und 40" in (5) entsprechen. Tabelle 1 . Ausgewahlte 'H-NMR-Daren der Verbindungen (4)-(9) (in CDCL). Verb. 6-Werte [a] Kopplungen [Hz] H' H2 H'" H3' J1.2 J2.3,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

1980
1980
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Dreifach acylierte 2-Amino-benzimidazole konnten in der symmetrischen Form D6 oder unsymmetrischen Form D7 vorliegen, vg1. (7). Beide Typen konnen leicht durch die oben erwahnten Symmetrieunterschiede in den NMR-Spektren charakterisiert werden [12].…”
Section: N-triacylierte Amino-benzimidazoleunclassified
See 1 more Smart Citation
“…Dreifach acylierte 2-Amino-benzimidazole konnten in der symmetrischen Form D6 oder unsymmetrischen Form D7 vorliegen, vg1. (7). Beide Typen konnen leicht durch die oben erwahnten Symmetrieunterschiede in den NMR-Spektren charakterisiert werden [12].…”
Section: N-triacylierte Amino-benzimidazoleunclassified
“…Die Derivate H2a und H4a lassen sich auch IR-spektroskopisch voneinander unterscheiden. Staab[7] untersuchte ebenfalls die Acetylierung von H mit Acetylchlorid und isolierte die beiden Isomere H2 a und H4 a. Er fand, dalj sich die Car-…”
unclassified
“…[3a] Only few compounds of this type have previously in 1980, [4] the focus of attention has gradually shifted been prepared using preformed mono-or bifunctionalised towards the development of more complex tetrathiafulvatetrathiafulvalenes. Thus, although a lot of complex mollene systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the reaction of 5-amino-l,2,4-triazole with acetylating reagents can give several products, depending on the nitrogen atom(s) that has(have) been acetylated (Staab & Seel, 1959). The end product of thermal rearrangement or of hydrolysis in boiling water of these compounds is 3-acetylamino-l,2,4-triazole (hereafter abbreviated to aat), as investigated by van den Bos (1960).…”
mentioning
confidence: 99%